Dampak Sistem Internet Banking Terhadap Risiko Bank Di Indonesia Periode 2009-2013 (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
Internet banking is an innovation process of the banking industry with the aim to enhance the operational activities of the banks and that proved to reduce the risk of bank. To determine the risk of banks in Indonesia can be determined using the ratio of NPA. Internet banking without the bank is worth the price higher than average risk to the banks internet banking. The indicates that the higher the risk, the higher the portion of assets that are not productive. The purpose of this study was to test the effect of the application of internet banking to bank risk. The study sample consisted of 109 banks in Indonesia from 2009 to 2013. Analysis tools used to test the effects of variable internet banking, the size of the bank, and the equity to risk used panel data regression. The results of this study indicate that the adoption of Internet banking is considered capable of lowering the credit risk of negative effects and significant. While variable size (size) showed a negative results and significant result, while equity significant positive effect on the regression model FEM.